The Effect of Macroeconomic Fundamentals, Capital Structure, Good Corporate Governance, and Firm Size on Financial Performance with Earnings Management as an Intervening Variable: Evidence from Primary Consumer Goods Companies Listed on the Indonesia Stock Exchange (2020–2024) - Devi Nadia Agustina; Hwihanus Hwihanus (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the effect of macroeconomic fundamentals, capital structure, Good Corporate Governance, and firm size on financial performance with earnings management as an intervening variable in primary consumer goods companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research applies a quantitative approach using purposive sampling, resulting in a final sample of four companies. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that capital structure has a significant negative effect on financial performance, while firm size has a significant positive effect on earnings management. Macroeconomic fundamentals, Good Corporate Governance, and firm size do not have a significant direct effect on financial performance. In addition, earnings management does not mediate the relationship between macroeconomic fundamentals, capital structure, Good Corporate Governance, and firm size on financial performance, as all indirect effect p-values exceed 0.05. The R-square values indicate that the model explains 22.8% of the variance in earnings management and 49.1% of the variance in financial performance, while the remaining variation is attributable to factors outside the proposed model.